Moderation-Mediation Effects in Bilingualism and Cognitive Reserve - Heredia, Roberto R.; Blackburn, Angélique M.; Vega, Luis A. (Frontiers in Psychology, 2020)
We first provide a critical review of the existing findings on bilingualism as a contributor to cognitive reserve from a moderator-mediator warranting cause-effect research conclusions. We next address the question of direct or indirect effects between bilingualism and neurocognitive protective factors influencing the associated age-related mental deficits. The existing findings support bilingualism as a predictor and as a moderator. Third, we propose cognitive reserve models of bilingualism describing analytical approaches that allow testing of these models and hypotheses related to path strength and causal relationships between predictors, moderators and mediators. Lastly and most importantly, we suggest using large datasets available via open repositories. This can aid in the testing of theoretical models, clarifying the roles of moderators, mediators, and assessing the research viability of multi-causal paths that can influence cognitive reserve. Creating collaborative datasets to test these models would greatly advance our field and identify critical variables in the study of the bilingual, aging brain.